THE LEGAL STRATEGY OF TREATING TELEMATICS CRIMES IN THE FIELD OF ELECTRONIC TRANSACTIONS IN GLOBAL TRADE - Dian Alan Setiawan; Abdul Rohman; Fabian Fadhly Jambak; Alfiyan Umbara; Mia Oktafiani Mulia Oktafiani Mulia (UNISSULA, 2021)
Economic globalization that is sweeping the world today began with the development of transportation facilities and cross-border trade. One of the facilities in the internet world to support economic activity is Electronic Transactions. In Indonesia, problems that arise due to the use of transaction media through telematics technology continue without being followed by the existence of laws that regulate it (cyber law). This study aims to determine legal policies against crime in electronic transaction activities in various sources of positive criminal law in Indonesia and to determine strategies for overcoming telematics crimes in the field of electronic transactions in global trade. This research is a normative legal research that is finding a rule of law, legal principles, and legal doctrines in order to answer the legal issues faced. The results of this study explain the legal policy against crime in electronic transaction activities in various sources of positive criminal law in Indonesia carried out in two stages, namely the Applicative Stage and the Formulation Stage and explain the Legal Strategy for Combating Telematics Crime in the Field of Electronic Transactions in Global Trade which is carried out through the Penalty Policy and non-penal policy.